Treatment of keloids through Runx2 siRNA-induced inhibition of the PI3K/AKT signaling pathway - Lv, Wenchang (Mol Med Rep, 2021)
Keloids are a skin fibroproliferative condition characterized by the hyperproliferation of fibroblasts and the excessive deposition of extracellular matrix (ECM) components. Previous studies have determined that Caveolin-1 controlled hyperresponsiveness to mechanical stimuli through Runt-related transcription factor 2 (Runx2) activation in keloids. However, the molecular mechanism of Runx2 regulating the pathological progression of keloids has not been elucidated. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that most of the differentially expressed genes (DEGs), including Runx2, were significantly enriched in the biological processes ‘Positive regulation of cell proliferation’, in the cellular components ‘Extracellular matrix’, in the molecular functions ‘Extracellular matrix structural constituents’ and in the KEGG ‘PI3K-Akt signaling pathway’. The aim of the present study was to investigate the expression levels of the Runx2 in human keloid tissues and primary human keloid fibroblasts (HKFs), and to determine the underlying molecular mechanisms involved in the fibrotic roles of Runx2 in keloid formation. Runx2 expression levels were analyzed in patient keloid tissues and HKFs using western blotting, reverse transcription-quantitative PCR (RT-qPCR) and immunofluorescence microscopy. Primary HKFs were transfected with a small interfering RNA (si) specifically targeting Runx2 (si-Runx2). Subsequently, Cell Counting Kit-8, wound healing and Transwell assays, flow cytometry, RT-qPCR and western blotting were applied to evaluate the proliferation, migration, apoptosis, ECM deposition and PI3K/AKT signaling pathway of HKFs, respectively. In addition, western blotting was also used to determine the expression levels of phosphorylated AKT and PI3K in HKFs. The results revealed that Runx2 expression levels were upregulated in keloid tissues and primary HKFs compared with the normal skin tissues and human normal fibroblasts. Following the transfection with si-Runx2, the proliferative and migratory abilities of HKFs were significantly reduced and the apoptotic rate was increased. The expression levels of type I, type III collagen, fibronectin, and α-smooth muscle actin were downregulated in si-Runx2-transfected cells, which was hypothesized to occur through following the downregulation of the phosphorylation levels of PI3K and AKT. In conclusion, the findings of the present study indicated that Runx2 silencing in HKFs might significantly inhibit the cell proliferation, migration and the expression levels of ECM-related proteins, and promote apoptosis via suppressing the PI3K/AKT signaling pathway. Thus, Runx2 siRNA treatment may reverse the pathological phenotype of keloids through the inhibition of PI3K/AKT signaling in patients.